2017
DOI: 10.1007/s10096-017-2986-8
|View full text |Cite
|
Sign up to set email alerts
|

The use of rapid test QuikRead go® Strep A in bacterial pharyngotonsillitis diagnosing and therapeutic decisions

Abstract: Group A Streptococci (GAS) are the main causative agents of bacterial pharyngitis, which require antibiotic therapy. Rapid diagnostic tests detecting GAS combined with Centor/McIsaac score enable accurate differential diagnosis (viral vs. bacterial) and prompt commencement of targeted treatment. The aim of this study was to assess the specificity, sensitivity, PPV and NPV of QuikRead go® Strep A (Orion Diagnostica Oy, Finland) recommended for the detection of GAS in pharyngeal swabs. Quick diagnostic test resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(44 citation statements)
references
References 20 publications
1
42
0
1
Order By: Relevance
“…The searches identified 80 citations. The full selection process (outlined in Figure 1) resulted in 18 studies 2,6,11,12,[24][25][26][27][28][29][30][31][32][33][34][35][36][37] being included in the review; 10 of these used the Centor score 2,11,12,[24][25][26][27][28][29][30][31] and eight used the McIsaac score. 6,11,12,[32][33][34][35][36][37] Only one study -reported by Fine et al 11,12 -provided sufficient data to allow a direct comparison between the two tests.…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…The searches identified 80 citations. The full selection process (outlined in Figure 1) resulted in 18 studies 2,6,11,12,[24][25][26][27][28][29][30][31][32][33][34][35][36][37] being included in the review; 10 of these used the Centor score 2,11,12,[24][25][26][27][28][29][30][31] and eight used the McIsaac score. 6,11,12,[32][33][34][35][36][37] Only one study -reported by Fine et al 11,12 -provided sufficient data to allow a direct comparison between the two tests.…”
Section: Study Selectionmentioning
confidence: 99%
“…Of those studies using the Centor score, eight were conducted in Europe 2, [24][25][26][27][29][30][31] and two in the US. 11,12,28 Of those studies using the McIsaac score, three were conducted in Europe, 32,33,36 four in North America, 6,11,12,35,37 and one in Australia. 34 Three studies were translated from Spanish.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional help can be obtained in differentiation between viral and bacterial pharyngitis by using the so-called Centor/McIsaac score, which is based on clinical signs and symptoms. Good correlation was shown between positive streptococcal test, culture and high score (Stefaniuk et al, 2017). Fewer than half of the Polish physicians participating in our study were not acquainted with this score however they claimed to know the Recommendation.…”
Section: Discussionmentioning
confidence: 58%
“…These tests have a high specificity, and negative predictive value (51). In recent years, similar chromogenic tests have been developed in order to detect the production of extended-spectrum beta-lactamase (ESBL) by Enterobacteriaceae.…”
Section: Rapid Chromogenic Testsmentioning
confidence: 99%